ADHD and hyperactivity: The influence of cognitive processing demands on gross motor activity level in children. Issue 1 (2nd January 2021) - Dekkers, Tycho J.; Rapport, Mark D.; Calub, Catrina A.; Eckrich, Samuel J.; Irurita, Carolina
ABSTRACT: Excessive gross motor activity is a prominent feature of children with ADHD, and accruing evidence indicates that their gross motor activity is significantly higher in situations associated with high relative to low working memory processing demands. It remains unknown, however, whether children's gross motor activity rises to an absolute level or accelerates incrementally as a function of increasingly more difficult cognitive processing demands imposed on the limited capacity working memory (WM) system – a question of both theoretical and applied significance. The present investigation examined the activity level of 8- to 12-year-old children with ADHD ( n = 36) and Typically Developing (TD) children ( n = 24) during multiple experimental conditions: a control condition with no storage and negligible WM processing demands; a short-term memory (STM) storage condition; and a sequence of WM conditions that required both STM and incrementally more difficult higher-order cognitive processing. Relative to the control condition, all children, regardless of diagnostic status, exhibited higher levels of gross motor activity while engaged in WM tasks that required STM alone and STM combined with upper level cognitive processing demands, and children with ADHD were motorically more active under all WM conditions relative to TD children. The increase in activity as a consequence of cognitive demand was similar for all experimental conditions. Findings suggest that upregulation of physical movement rises and remains relatively stable to promote arousal related mechanisms when engaged in cognitive activities involving WM for all children, and to a greater extent for children with ADHD.